Obesity Enhances the Conversion of Adipose-Derived Stromal/Stem Cells into Carcinoma-Associated Fibroblast Leading to Cancer Cell Proliferation and Progression to an Invasive Phenotype - Amy L. Strong; Dorothy T. Pei; Christian G. Hurst; Jeffrey M. Gimble; Matthew E. Burow; Bruce A. Bunnell (Hindawi Limited, 2017)
Obesity is associated with enhanced tumor growth and progression. Within the adipose tissue are adipose-derived stromal/stem cells (ASCs) that have been shown to convert into carcinoma-associated fibroblast (CAFs) in the presence of tumor-derived factors. However, the impact of obesity on the ASCs and on the conversion of ASCs into CAFs has not been demonstrated. In the current study, ASCs isolated from lean donors (BMI < 25; lnASCs) were compared with ASCs isolated from obese donors (BMI > 30, obASCs). The contribution of tumor-derived factors on the conversion of ASCs to CAFs was investigated. Following exposure to cancer cells, obASCs expressed higher levels of CAF markers, including NG2, alpha-SMA, VEGF, FAP, and FSP, compared to lnASCs. To investigate the crosstalk between ASCs and breast cancer cells, MCF7 cells were serially cocultured with lnASCs or obASCs. After coculture with lnASCs and obASCs, MCF7 cells demonstrated enhanced proliferation and expressed an invasive phenotype morphologically, with more pronounced effects following exposure to obASCs. Long-term exposure to obASCs also enhanced the expression of protumorgenic factors. Together, these results suggest that obesity alters ASCs to favor their rapid conversion into CAFs, which in turn enhances the proliferative rate, the phenotype, and gene expression profile of breast cancer cells.